Lipopolysaccharide Inhibits Autophagy and Promotes Inflammatory Responses via p38 MAPK-Induced Proteasomal Degradation of Atg13 in Hepatic Stellate Cells - Yuchao Wu; Yajuan He; Fei Wang; Naijuan Yao; Yingren Zhao; Zhen Tian (Mediators of Inflammation)
Background. Inflammation plays a critical role in the progression of acute-on-chronic liver failure (ACLF). Atg13 is a vital regulatory component of the ULK1 complex, which plays an essential role in the initiation of autophagy. Previously, hepatic stellate cells (HSCs) were considered to be noninflammatory cells that contribute only to hepatic fibrosis. Recently, it has been found that HSCs can secrete inflammatory cytokines and participate in hepatic inflammation. Autophagy and proteasome-mediated degradation constitute two major means of protein turnover in cells. Autophagy has been shown to regulate inflammation, but it is unclear whether ubiquitin (Ub)-proteasome system (UPS) is involved in inflammatory responses in HSCs during ACLF. Methods. Clinical data were collected from ACLF patients, and surgically resected paraffin-embedded human ACLF liver tissue specimens were collected. The expression of Atg13 was assessed by quantitative real-time polymerase chain reaction (qRT-PCR) and Western blotting. Secretion of IL-1β was assessed by ELISA. Atg13 was knocked down by siRNA in LX2 cells. Coimmunoprecipitation assay was used to detect protein binding and polyubiquitination of Atg13. In vitro tests with LX2 cells were performed to explore the effects and regulation of p38 MAPK, Atg13, UPS, autophagy, and inflammation. Results. Serum lipopolysaccharide (LPS) was positively associated with disease severity in ACLF patients, and p38 MAPK was overexpressed in ACLF liver tissue. We evaluated the role of Atg13 in HSC inflammation and explored the possible underlying mechanisms. Inflammatory factors were upregulated via activation of p38 MAPK and inhibition of autophagy in LX-2 cells. Expression of Atg13 was decreased in LPS-incubated LX2 cells. Atg13 knockdown markedly inhibited autophagy and promoted LPS-induced inflammation in LX2 cells. Our in vitro experiments also showed that LPS induced depletion of Atg13 via UPS, and this process was dependent on p38 MAPK. Conclusions. LPS induces proteasomal degradation of Atg13 via p38 MAPK, thereby participating in the aggravation of LPS-induced autophagy inhibition and inflammatory responses in LX2 cells. Atg13 serves as a mediator between autophagy and proteasome. Modulation of Atg13 or proteasome activity might be a novel strategy for treating HSC inflammation.